Tensions in Teaching about Teaching Understanding Practice as a Teacher Educator - Berry, Amanda (Self-Study of Teaching and Teacher Education Practices, 2008)
This series in Teacher Education: Self-study of Teacher Education Practices (S-STEP) has been created in order to offer clear and strong examples of self-study of teaching and teacher education practices. It explicitly values the work of teachers and teacher educators and through the research of their practice, offers insights into new ways of encouraging educational change. The series is designed to complement the Inter- tional Handbook of Self-study of Teaching and Teacher Education practices (Loughran, Hamilton, LaBoskey, & Russell, 2004) and as such, helps to further define this important field of teaching and research. Self-study of teaching and teacher education practices has become an important 'way in'to better understanding the complex world of teaching and learning about teaching. The questions, issues and concerns, of teacher educators in and of their own practice are dramatically different to those raised by observers of the field. Hence, self-study can be seen as an invitation to teacher educators to more meani- fully link research and practice in ways that matter for their pedagogy and, as a consequence, their students'learning about pedagogy.